* ROBOT & THE END: A Comparative Critical Reading of the Staging of Synthesized Voices in Digital Media Performances - Hasse Jørgensen, Stina (Peripeti, 2018)
In this article, I present a critical comparative reading of the experiences of gender promoted by media performances that make use of synthesized voices in relation to the 3D animated vocaloid performance THE END (2012) and the multimedia dance performance ROBOT (2013). I argue that the staging of synthesized voices in THE END promotes a gender performativity of the heteronormative gender binary, creating a sexualized fetishization of the technological body. ROBOT, on the other hand, as a media performance utilizes the audio-visual bsody of a little robot to subvert gender stereotypes, demonstrating that the visual contextualization and framing of the synthesized voice matters in the representation of identities in digital media performances.